Vanadium Toxicity Is Altered by Global Warming Conditions in Sea Urchin Embryos: Metal Bioaccumulation, Cell Stress Response and Apoptosis - Chiara Martino; Fabiana Geraci; Rosaria Scudiero; Giampaolo Barone; Flores Naselli; Roberto Chiarelli (MDPI AG, 2024)
In recent decades, the global vanadium (V) industry has been steadily growing, together with interest in the potential use of V compounds as therapeutics, leading to V release in the marine environment and making it an emerging pollutant. Since climate change can amplify the sensitivity of marine organisms already facing chemical contamination in coastal areas, here, for the first time, we investigated the combined impact of V and global warming conditions on the development of Paracentrotus lividus sea urchin embryos. Embryo-larval bioassays were carried out in embryos exposed for 24 and 48 h to sodium orthovanadate (Na3VO4) under conditions of near-future ocean warming projections (+3 °C, 21 °C) and of extreme warming at present-day marine heatwave conditions (+6 °C, 24 °C), compared to the control temperature (18 °C). We found that the concomitant exposure to V and higher temperature caused an increased percentage of malformations, impaired skeleton growth, the induction of heat shock protein (HSP)-mediated cell stress response and the activation of apoptosis. We also found a time- and temperature-dependent increase in V bioaccumulation, with a concomitant reduction in intracellular calcium ions (Ca2+). This work demonstrates that embryos' sensitivity to V pollution is increased under global warming conditions, highlighting the need for studies on multiple stressors.